Atomic-force Microscopy and Its Applications - Tański, Tomasz; Staszuk, Marcin; Ziębowicz, Bogusław (IntechOpen, 2019)
Atomic force microscopy is a surface analytical technique used in air, liquids or a vacuum to generate very high-resolution topographic images of a surface, down to atomic resolution. This book is not only for students but also for professional engineers who are working in the industry as well as specialists. This book aims to provide the reader with a comprehensive overview of the new trends, research results and development of atomic force microscopy. The chapters for this book have been written by respected and well-known researchers and specialists from different countries. We hope that after studying this book, you will have objective knowledge about the possible uses of atomic force microscopy in many scientific aspects of our civilisation.